Use of Systemic Therapies for Treatment of Psoriasis in Patients with a History of Treated Solid Tumours: Inference-Based Guidance from a Multidisciplinary Expert Panel - Kim A. Papp; Barbara Melosky; Sandeep Sehdev; Sebastien J. Hotte; Jennifer R. Beecker; Mark G. Kirchhof; Irina Turchin; Jan P. Dutz; Melinda J. Gooderham; Robert Gniadecki; Chih-ho Hong; Jo Lambert; et al. (Adis, Springer Healthcare, 2023)
Abstract Background Patients with treated solid tumours (TSTs) are a highly heterogeneous population at an increased risk for malignancy compared with the general population. When treating psoriasis in patients with a history of TSTs, clinicians are concerned about the immunosuppressive nature of psoriasis therapies, the possibility of augmenting cancer recurrence/progression, and infectious complications. No direct, high-level evidence exists to address these concerns. Objectives We aim to provide a structured framework supporting healthcare professional and patient discussions on the risks and benefits of systemic psoriasis therapy in patients with previously TSTs. Our goal was to address the clinically important question, "In patients with TSTs, does therapy with systemic agents used for psoriasis increase the risk of malignancy or malignancy recurrence?" Methods We implemented an inference-based approach relying on indirect evidence when direct clinical trial and real-world data were absent. We reviewed indirect evidence supporting inferences on the status of immune function in patients with TSTs. Recommendations on systemic psoriasis therapies in patients with TSTs were derived using an inferential heuristic. Results We identified five indirect indicators of iatrogenic immunosuppression informed by largely independent bodies of evidence: (1) overall survival, (2) rate of malignancies with psoriasis and systemic psoriasis therapies, (3) rate of infections with psoriasis and systemic psoriasis therapies, (4) common disease biochemical pathways for solid tumours and systemic psoriasis therapies, and (5) solid organ transplant outcomes. On the basis of review of the totality of this data, we provided inference-based conclusions and ascribed level of support for each statement. Conclusions Prior to considering new therapies for psoriasis, an understanding of cancer prognosis should be addressed. Patients with TSTs and a good cancer prognosis will have similar outcomes to non-TST patients when treated with systemic psoriasis therapies. For patients with TSTs and a poor cancer prognosis, the quality-of-life benefits of treating psoriasis may outweigh the theoretical risks.